THE ROLE OF PRODUCT INNOVATION AS A MEDIATOR WITH GREEN TECHNOLOGY ON BUSINESS PERFORMANCE IN BATIK MSMES - Firdaus teguh Wicaksono; Fazlurrahman, Hujjatullah; Abrori, Nanang Hoesen Hidroes; Rahman, M. Fajar Wahyudi (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
This study aims to analyze the effect of green technology adoption on business performance through product innovation in batik micro, small, and medium enterprises (MSMEs) in Lumajang Regency. A quantitative explanatory approach was employed. Data were collected through a structured questionnaire survey of 50 batik MSMEs selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). that green technology adoption positively affects business performance and product innovation. Product innovation also positively influences business performance and partially mediates the relationship. These findings show that environmentally friendly technology improves operational efficiency and stimulates value-added product innovation. The novelty lies in examining product innovation as a mediating variable in batik MSMEs located in a non-industrial-center area. The originality is reflected in integrating green technology, product innovation, and business performance into a single mediation model using PLS-SEM. This study concludes that green technology adoption, supported by product innovation, significantly enhances batik MSMEs’ business performance.